2011
DOI: 10.1007/s00268-011-1069-8
|View full text |Cite
|
Sign up to set email alerts
|

How Radical Should Surgery Be for Early Esophageal Cancer?

Abstract: Limited resection leads to lower lymph node yield but similar oncologic effectiveness as the extensive surgery. It may represent a valuable alternative in the treatment of patients with early (submucosal) esophageal carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 73 publications
2
7
0
Order By: Relevance
“…Therefore, endoscopic resection is limited to patients with high-grade dysplasia or mucosal tumors (Korn, 2004), especially for patients with high-grade dysplasia, as no lymph node metastases and systemic disease reported. Most of the previous studies confirmed that lymph node metastases were rare in patients with mucosal tumor (Endo et al, 2000;Fujita et al, 2001;DeMeester, 2010;Bogoevski et al, 2011), but some studies reported a rate of higher than ten percent for lymph node metastases in mucosal tumor (Matsubara et al, 1999). It is hard to identify patients with high risk of lymph node metastases in mucosal tumor in our study as only one of the 62 patients with mucosal tumor had lymph node metastases (1.6%).…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Therefore, endoscopic resection is limited to patients with high-grade dysplasia or mucosal tumors (Korn, 2004), especially for patients with high-grade dysplasia, as no lymph node metastases and systemic disease reported. Most of the previous studies confirmed that lymph node metastases were rare in patients with mucosal tumor (Endo et al, 2000;Fujita et al, 2001;DeMeester, 2010;Bogoevski et al, 2011), but some studies reported a rate of higher than ten percent for lymph node metastases in mucosal tumor (Matsubara et al, 1999). It is hard to identify patients with high risk of lymph node metastases in mucosal tumor in our study as only one of the 62 patients with mucosal tumor had lymph node metastases (1.6%).…”
Section: Discussionmentioning
confidence: 53%
“…Due to the improvement of endoscopy and staining methods, the detection rate of EEC in our hospital rose significantly in the past five years, and reached to nearly 10%. But the detection rate is still lower than that of 15%-30% in Japan and western countries (Natsugoe et al, 2004;Stein et al, 2005;Saha et al, 2009;Bogoevski et al, 2011;Dubecz et al, 2012).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A large number of studies analyzing the results of surgical treatment of ESCC involve cohorts that also comprise esophageal adenocarcinoma 3,9,15,18,23,33,36,37,38 . Moreover, several studies do not discriminate the results of esophagectomy by tumor type (ESCC vs. esophageal carcinoma).…”
Section: Discussionmentioning
confidence: 99%
“…Proximal gastrectomy combined with jejunal interposition reconstruction has become an ideal choice for the treatment of for Siewert II and III AEG, since studies have shown that it can ensure the surgical safety, achieve an ideal radical cure, and achieve comparable 5-year overall survival with TG [5–7]. In China, piggyback jejunal interposition reconstruction (PJIR), proposed by Shanxi Tumor Hospital, was performed on the basis of Roux-en-Y jejunal anastomosis on the jejunum of the esophagus, and then jejunal remnant jejunostomy was performed on the appropriate location of jejunum loop.…”
Section: Introductionmentioning
confidence: 99%